The mid-century model of critical thinking: Shah Wali Allah Al-Dihlawi - Noraini Junoh,; Abdul Manam Mohamad,; Nor Asmira Mat Jusoh,; Zanirah Mustafa @ Busu, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Muslims are very proud of the emergence of scholars of the past who have made tremendous contributions both to the Islamic and Western worlds. However, such glory and pride are undervalued as no serious efforts have been made to refine and apply to the tee all the contributions by past scholars in the efforts to rebuild the superior Islamic civilization. Hence, this article aims to introduce an authoritative figure in the Middle Ages who applied critical thinking especially in the field of Islamic knowledge that has greatly impacted Muslims worldwide. He is Shah Wali Allah al-Dihlawi who was an influential and prominent Indian Islamic scholar in the 18th century AD. This study is qualitative library research, using inductive, deductive and comparative methods in analyzing data related to the biography and intellectuality of Shah Wali Allah in the field of critical thinking. The findings found that Shah Wali Allah can be used as an example or model of medieval critical thinking that has brought about major changes in the field of Islamic science. He also prepared a critical thinking manhaj that is in line with the revelations thus making him comparable to other scholars of the past.